Residual oil hydrogenation catalyst grading method and application thereof
By filling different functions catalysts with grade and matching methods in the hydrogen hydrogenation reaction, especially the hydrogen decarcus catalyst composed of modified carriers and active metals, the problem of insufficient activity and stability of the existing catalysts has been solved. Efficient sulfur and nitrogen removal.
Patent Information
- Application Number
- CN202310920344.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-07-26
AI Technical Summary
The existing residual oil hydrogenation catalysts have insufficient activity and stability in desulfurization and denitrification, and the small pores are not conducive to the diffusion of macromolecules.
A grade method is used to fill the hydrogen refreshing protective agent, hydrogen dehydration metal catalyst, hydrogen dehydration catalyst, and hydrogenation nitrogen dehydration catalyst along the direction of liquid -phase logistics. The hydrogen deoxymal catalyst is composed of carriers (镓 and fluorine aluminum alumina) and active metals. Active metals include the VIII and VIB metals.
The deep conversion of sulfides and nitride in asphalt quality has been realized. The hydrogenation activity is high, good stability, and the pore structure, acid quantity and acid distribution of the catalysts are appropriate, which improves the performance of accumulation.
Smart Images

Figure BDA0004358476720000171 
Figure BDA0004358476720000181 
Figure BDA0004358476720000191
Abstract
Description
Technical Field
[0001] The invention belongs to the field of residual oil hydrogenation, and in particular relates to a grading method of a residual oil hydrogenation catalyst and application thereof. Background Art
[0002] In recent years, the processing proportion of heavy and inferior crude oil in oil refining has been increasing. Residue oil hydrotreating technology can convert as much heavy and inferior crude oil into high-quality finished oil and chemical raw materials as possible, and is the main technical means for processing residue oil in refineries. Among them, the fixed-bed residue oil hydrotreating process can meet the needs of adapting to the inferior quality of raw materials and long-term stable operation. It is the most mature, reliable and widely used process, accounting for 3 / 4 of the total residue oil hydrotreating processing capacity.
[0003] The composition of residual oil raw materials is complex and difficult to process. Catalysts with different properties are needed to remove most of the impurities such as metals, sulfur, nitrogen, etc., and to achieve hydrogenation conversion of residual carbon precursors and increase the hydrogen content. Fixed-bed residual oil hydrogenation catalysts can be divided into protective agents, demetallizing agents, desulfurizing agents and residual carbon removal agents according to their functions. Catalysts of different properties and types are usually filled in different parts of the reactor by graded filling. According to the properties of the raw materials, operating conditions and requirements for product quality, the operation cycle of the residual oil hydrogenation unit can be extended by using catalysts in a reasonable graded manner and distributing the reaction load in a reasonable manner. The basic principle of grading is that the catalyst particle size is from large to small, the average pore size is from large to small, the porosity is from large to small, and the activity is from low to high along the direction of liquid phase flow.
[0004] CN1458236A discloses a method for preparing a heavy oil hydrodemetallization and desulfurization catalyst. The catalyst preparation method uses two aluminum-containing materials in different forms, one is calcined aluminum oxide, and the other is aluminum hydroxide dry rubber powder, with alkali metal and / or alkaline earth metal elements as auxiliary agents, the auxiliary agent is partially premixed with the aluminum hydroxide dry rubber powder, and partially loaded on the catalyst by an impregnation method, so that the auxiliary agent is unevenly distributed on the catalyst. The average pore size of the catalyst obtained by the method is 15-19nm, which is still too small for asphaltene micelles, is not conducive to residual oil hydrodesulfurization and hydrodemetallization reactions, and its activity and stability need to be further improved.
[0005] CN1098433A discloses a method for preparing a hydrorefining catalyst. The method is to mix powdered basic nickel carbonate into the extrusion process of alumina monohydrate to provide the Ni content required by the catalyst, and at the same time mix a small amount of powdered industrial-grade ammonium molybdate, and then immerse the molybdenum ammonia solution once to prepare the final catalyst. The catalyst prepared by this method has a high hydrodenitrification performance, but the pores are too small to be conducive to the diffusion of macromolecules, and the metal cannot be precipitated inside the pores.
[0006] CN1257103A discloses a method for preparing a hydrogenation catalyst. The method optimizes the kneading process of aluminum hydroxide monohydrate and metal salts to promote metal dispersion. After all materials are kneaded into a plastic body, they are extruded and formed into strips, and then activated by steam-air high temperature to prepare a catalyst. The catalyst prepared by this method has too small pores, and it is impossible to prepare a dual-function catalyst with both denitrification performance and high tolerance to metal impurities. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a grading method for a residue oil hydrogenation catalyst and its application. The grading method is used for residue oil hydrogenation reaction and has a significant effect of deep desulfurization and denitrification.
[0008] The first aspect of the present invention provides a grading method for a residue oil hydrogenation catalyst, which comprises: sequentially filling a hydrogenation protective agent, a hydrodemetallization catalyst, a hydrodesulfurization catalyst and a hydrodenitrogenation catalyst along the flow direction of a liquid phase stream.
[0009] According to the present invention, the hydrodesulfurization catalyst includes a carrier and an active metal component, wherein the carrier includes gallium- and fluorine-modified metakaolin and alumina in a mass ratio of 15 to 30:7 to 13, and the mass content of gallium in the gallium- and fluorine-modified metakaolin is 2.0% to 5.0%, and the mass content of fluorine is 0.8% to 1.5%.
[0010] According to the present invention, in the hydrodesulfurization catalyst, the active metal includes at least one metal component selected from Group VIII and at least one metal component selected from Group VIB; the Group VIII metal is preferably nickel and / or cobalt; the Group VIB metal is preferably molybdenum and / or tungsten.
[0011] According to the present invention, in the hydrodesulfurization catalyst, based on the mass of the catalyst, the mass content of the carrier is 75% to 85%, the content of Group VIII as oxide is 2% to 6%, and the content of Group VIB metal as oxide is 10% to 20%.
[0012] According to the present invention, the properties of the hydrodesulfurization catalyst are as follows: the specific surface area is 180 to 220 m 2 / g, the pore volume is 0.5~0.7mL / g, and the average pore diameter is 10.0~30.0nm.
[0013] According to the present invention, the hydrodesulfurization catalyst is a shaped body, and its shape can be the shape commonly used by fixed bed hydrogenation catalysts, such as at least one of strip, clover, four-leaf clover, sphere, and cylinder. The particle size of the hydrodesulfurization catalyst is 2 to 10 mm, preferably 2.5 to 8.0 mm.
[0014] According to the present invention, the method for preparing the hydrodesulfurization catalyst comprises:
[0015] (1) mixing metakaolin, gallium nitrate, ammonium fluoride and water, sealing and hydrothermally treating, drying and calcining to obtain a modified material;
[0016] (2) kneading the modified material obtained in step (1), pseudo-boehmite, an adhesive, an extrusion aid, a pore-enlarging agent and water, drying and calcining to obtain a catalyst carrier;
[0017] (3) preparing an impregnation solution containing amines, alcohols, thiourea and active metals;
[0018] (4) The catalyst carrier obtained in step (2) is impregnated with the impregnation solution obtained in step (3), and the catalyst carrier is dried and calcined to obtain a hydrodesulfurization catalyst.
[0019] According to the present invention, in the preparation method of the hydrodesulfurization catalyst, the mass ratio of the gallium nitrate and ammonium fluoride in step (1) is 1 to 10:1, and the total mass of the gallium nitrate and ammonium fluoride accounts for 5% to 60% of the mass of the metakaolin, preferably 15% to 40%; and / or, the amount of water added in step (1) is added at a mass ratio of water to the total mass of the metakaolin, gallium nitrate and ammonium fluoride of 5:1 to 10:1. The metakaolin, gallium nitrate, ammonium fluoride and water can be added and mixed in any order, for example, water can be added to a mixture of metakaolin, gallium nitrate and ammonium fluoride, or metakaolin can be immersed in an aqueous solution of gallium nitrate and ammonium fluoride.
[0020] According to the present invention, in the preparation method of the hydrodesulfurization catalyst, the conditions of the sealed hydrothermal treatment in step (1) are as follows: the hydrothermal treatment temperature is 80 to 130°C, and the time is 3 to 10 hours; wherein the heating rate is 3 to 10°C / min. The sealed hydrothermal treatment is generally carried out in a high-pressure reactor under autogenous pressure. Preferably, the hydrothermal treatment adopts a two-stage hydrothermal treatment, and the temperature of the second stage is at least 20°C higher than the temperature of the first stage, preferably at least 30°C higher.
[0021] According to the present invention, in the preparation method of the hydrodesulfurization catalyst, the drying temperature in step (1) is 120-160° C., the drying time is 2-6 hours, the calcination temperature is 550-700° C., and the calcination time is 4-6 hours.
[0022] According to the present invention, in the preparation method of the hydrodesulfurization catalyst, the mass ratio of the pseudo-boehmite in step (2) to the modified material is 7 to 13:15 to 30 in terms of alumina. The adhesive can be at least one of nitric acid, acetic acid, and citric acid, the extrusion aid can be sesbania powder, and the pore expander can be one or more of graphite, activated carbon, sawdust, or cellulose. The amount of the adhesive and extrusion aid added is added according to the actual molding needs, and the present invention has no special requirements. The amount of the pore expander added is 4wt% to 13wt% of the total mass of the pseudo-boehmite in terms of alumina and the modified material.
[0023] According to the present invention, in the preparation method of the hydrodesulfurization catalyst, the drying temperature in step (2) is 120-160° C., the drying time is 2-6 hours, the roasting temperature is 550-750° C., and the roasting time is 2-6 hours. The molding can be performed by conventional molding methods, such as extrusion molding, tablet molding, etc.
[0024] According to the present invention, in the method for preparing the hydrodesulfurization catalyst, phosphoric acid may be added to the impregnation solution in step (3).
[0025] According to the present invention, in the preparation method of the hydrodesulfurization catalyst, the alcohol compound in step (3) is one or more of pentaerythritol, ethylene glycol, glycerol, 1,2-propylene glycol, 1,4-butanediol, and neopentyl glycol; the amine compound is one or more of hexamethylenetetramine, ethylenediamine, ethanolamine, diethanolamine, and triethanolamine; the mass ratio of the alcohol compound to the amine compound is 1:1 to 16:1; the amount of thiourea added is such that its concentration in the impregnation solution is 5 to 70 g / L, preferably 8 to 50 g / L; the concentration of the alcohol compound in the impregnation solution in step (3) is 5 to 60 g / L, preferably 7 to 30 g / L.
[0026] According to the present invention, in the method for preparing the hydrodesulfurization catalyst, the active metal in step (3) includes at least one metal component selected from Group VIII and at least one metal component selected from Group VIB. The Group VIII metal is preferably nickel and / or cobalt, and the Group VIB metal is preferably molybdenum and / or tungsten. The active metal in the impregnation solution in step (3) is calculated as metal oxide, wherein the content of Group VIB metal is 150 to 450 g / L, preferably 300 to 400 g / L, the content of Group VIII metal is 10 to 120 g / L, preferably 40 to 60 g / L, and the concentration of phosphorus is 20 to 80 g / L, preferably 40 to 60 g / L. The tungsten source can be tungstate or tungsten oxide, preferably ammonium metatungstate; the molybdenum source can be one or more of molybdenum trioxide, molybdate, and paramolybdate, preferably molybdenum trioxide; the nickel source can be one or more of nickel nitrate, nickel acetate, basic nickel carbonate, and nickel chloride, preferably basic nickel carbonate; the cobalt source can be one or more of cobalt nitrate, cobalt acetate, basic cobalt carbonate, and cobalt chloride, preferably basic cobalt carbonate. The phosphorus-containing compound is phosphoric acid.
[0027] According to the present invention, in the preparation method of the hydrodesulfurization catalyst, the impregnation in step (4) adopts a spray impregnation method, and the impregnation adopts equal volume impregnation or supersaturated impregnation. Preferably, after the impregnation, the sample is placed under closed conditions at room temperature for 6 to 12 hours before the drying step is performed; and / or, in step (4), the drying condition is a constant temperature of 100 to 160° C. for 1 to 8 hours; the roasting condition is a constant temperature of 450 to 650° C. for 2 to 7 hours, preferably a constant temperature of 480 to 600° C. for 2 to 7 hours.
[0028] According to the present invention, the hydrodenitrogenation catalyst comprises a carrier and an active metal component, wherein the carrier comprises a modified Y molecular sieve and alumina, wherein the modified Y molecular sieve is a small-grained mesoporous modified Y molecular sieve, and has the following properties: a crystal particle size of less than 500 nm, preferably 300 to 500 nm, a molar ratio of silicon oxide to alumina of 8 to 55, and a specific surface area of 640 to 800 m 2 / g, the unit cell parameters are 2.433~2.460nm, and the average pore size is 10~30nm.
[0029] According to the present invention, the sodium content in the modified Y molecular sieve is below 1 wt%.
[0030] According to the present invention, in the hydrodenitrogenation catalyst, the active metal comprises at least one metal component selected from Group VIII and at least one metal component selected from Group VIB; the Group VIII metal is preferably nickel and / or cobalt; the Group VIB metal is preferably molybdenum and / or tungsten.
[0031] According to the present invention, in the hydrodenitrogenation catalyst, based on the mass of the catalyst, the mass content of the carrier is 74% to 85%, the content of Group VIII as oxide is 2% to 6%, and the content of Group VIB metal as oxide is 15% to 24%.
[0032] According to the present invention, in the hydrodenitrogenation catalyst, based on the mass of the carrier, the content of the modified Y molecular sieve is 40% to 70%, and the content of the alumina is 14% to 40%.
[0033] According to the present invention, the properties of the hydrodenitrogenation catalyst are as follows: the specific surface area is 190 to 250 m 2 / g, the pore volume is 0.4~0.6mL / g, and the average pore diameter is 10~20nm.
[0034] According to the present invention, the hydrodenitrogenation catalyst is a molded body, and its shape can be the shape commonly used by fixed bed hydrogenation catalysts, such as at least one of strip, clover, four-leaf clover, sphere, and cylinder, and its particle size is 1.5-8mm, preferably 2.0-6.0mm.
[0035] According to the present invention, the method for preparing the hydrodenitrogenation catalyst comprises:
[0036] (1) The NaY molecular sieve is subjected to ammonium ion exchange, filtration and washing to obtain an NH4Y molecular sieve filter cake;
[0037] (2) mixing the NH4Y molecular sieve filter cake obtained in step (1) with an organic acid, a water-soluble polymer and water, and then performing a hydrothermal treatment to obtain a modified Y molecular sieve;
[0038] (3) kneading the modified Y molecular sieve obtained in step (2), pseudo-boehmite, an adhesive, an extrusion aid, a pore-enlarging agent and water into a mold, drying and calcining to obtain a catalyst carrier;
[0039] (4) impregnating the catalyst support obtained in step (3) into a gallium nitrate solution, drying it, and subjecting it to high-temperature steam treatment to obtain a catalyst support;
[0040] (5) preparing an impregnation solution containing amines, alcohols, thiourea and active metals;
[0041] (6) The catalyst carrier obtained in step (4) is impregnated with the impregnation solution obtained in step (5), and the mixture is dried and calcined to obtain a hydrodenitrogenation catalyst.
[0042] According to the present invention, in the method for preparing the hydrodenitrogenation catalyst, the properties of the NaY molecular sieve in step (1) are as follows: the molar ratio of silicon oxide to aluminum oxide is 3 to 7:1, and the sodium content is 6 wt% to 12 wt%.
[0043] According to the present invention, in the preparation method of the hydrodenitrogenation catalyst, step (1) NaY molecular sieve is subjected to ammonium ion exchange, wherein the NaY molecular sieve is mixed with an ammonium salt solution for slurrying, the pH value of the slurry is adjusted, the ammonium ion exchange is performed, and the NH4Y molecular sieve filter cake is obtained after filtering and washing; wherein the mass ratio of NaY molecular sieve: water: ammonium salt is 1: 6-25: 0.2-0.4; the pH value of the slurry is adjusted to 3-4; the ammonium ion exchange temperature is adjusted to 70-90°C, the ammonium ion exchange time is 2-4 hours, and the number of ammonium ion exchanges is 1-3 times. The ammonium salt may be one or more of ammonium chloride, ammonium nitrate, ammonium sulfate, and ammonium phosphate.
[0044] According to the present invention, in the method for preparing the hydrodenitrogenation catalyst, the filtering and washing in step (1) can be carried out by conventional methods, and the washing can be carried out by deionizing washing.
[0045] According to the present invention, in the method for preparing the hydrodenitrogenation catalyst, the organic acid in step (2) is selected from at least one of fumaric acid, adipic acid, tartaric acid, citric acid, oxalic acid, acetic acid, salicylic acid and malic acid. The water-soluble polymer is selected from at least one of polyvinyl alcohol, polyethylene oxide, polyvinyl pyrrolidone and water-soluble polysaccharides (such as methyl cellulose). The water-soluble polymer is selected from a polymer having a weight average molecular weight of 10,000 to 40,000.
[0046] According to the present invention, in the method for preparing the hydrodenitrogenation catalyst, the mass ratio of the NH4Y molecular sieve: organic acid: water-soluble polymer: water in step (2) is 1: 0.01-0.05: 0.05-0.25: 15-40.
[0047] According to the present invention, in the preparation method of the hydrodenitrogenation catalyst, the conditions of the hydrothermal treatment in step (2) are as follows: the temperature is 100-150°C, and the treatment time is 5-12h; wherein the heating rate is 8-15°C / min; preferably, the hydrothermal treatment adopts two-stage hydrothermal treatment, and the temperature of the second stage is at least 15°C higher than the temperature of the first stage, preferably at least 20°C; the hydrothermal treatment is generally carried out in a sealed high-pressure reactor, and the hydrothermal treatment is carried out under autogenous pressure. After the hydrothermal treatment in step (2), drying is carried out, and the drying conditions are as follows: the drying temperature is 100-160°C, and the drying time is 3-8 hours.
[0048] According to the present invention, in the preparation method of the hydrodenitrogenation catalyst, the mass ratio of the pseudo-boehmite in step (3) to the modified Y molecular sieve in terms of alumina is 7 to 13:15 to 30. The adhesive may be at least one of nitric acid, acetic acid, and citric acid, the extrusion aid may be sesbania powder, and the pore expander may be one or more of graphite, activated carbon, sawdust, or cellulose. The amount of the adhesive, extrusion aid, and water added is added according to the actual molding needs, and the present invention has no special requirements. The amount of the pore expander added is 2wt% to 10wt% of the total mass of the pseudo-boehmite in terms of alumina and the modified Y molecular sieve. The molding may be performed by conventional molding methods, such as extrusion molding, tablet molding, etc.
[0049] According to the present invention, in the preparation method of the hydrodenitrogenation catalyst, the drying temperature in step (3) is 120-160° C., the drying time is 3-6 hours, the calcination temperature is 550-700° C., and the calcination time is 2-6 hours.
[0050] According to the present invention, in the preparation method of the hydrodenitrogenation catalyst, the concentration of the gallium nitrate solution in step (4) is 0.5-2.5 mol / L; the impregnation method in step (4) is saturated impregnation or unsaturated impregnation; the conditions of the high-temperature steam treatment are as follows: the temperature is 500-700°C and the time is 60-90 min.
[0051] According to the present invention, in the method for preparing the hydrodenitrogenation catalyst, phosphoric acid may be added to the impregnation solution in step (5).
[0052] According to the present invention, in the preparation method of the hydrodenitrogenation catalyst, the alcohol compound in step (5) is one or more of pentaerythritol, ethylene glycol, glycerol, 1,2-propylene glycol, 1,4-butanediol, and neopentyl glycol; the amine compound is one or more of hexamethylenetetramine, ethylenediamine, ethanolamine, diethanolamine, and triethanolamine; the mass ratio of the alcohol compound to the amine compound is 1:1 to 16:1; the amount of thiourea added is such that its concentration in the impregnation solution is 5 to 70 g / L, preferably 8 to 50 g / L; in the impregnation solution in step (5), the concentration of the alcohol compound is 2 to 60 g / L, preferably 7 to 30 g / L.
[0053] According to the present invention, in the preparation method of the hydrodenitrogenation catalyst, the active metal in step (5) includes at least one metal component selected from Group VIII and at least one metal component selected from Group VIB. The Group VIII metal is preferably nickel and / or cobalt, and the Group VIB metal is preferably molybdenum and / or tungsten. In the impregnation solution in step (5), the active metal is calculated as metal oxide, wherein the content of Group VIB metal is 150 to 450 g / L, preferably 300 to 400 g / L, the content of Group VIII metal is 10 to 120 g / L, preferably 40 to 60 g / L, and the concentration of phosphorus is 20 to 80 g / L, preferably 40 to 60 g / L. The molybdenum source is one or more of molybdenum trioxide, molybdate, and paramolybdate, preferably molybdenum trioxide; the tungsten source is tungstate or tungsten oxide, preferably ammonium metatungstate; the nickel source is one or more of nickel nitrate, nickel acetate, basic nickel carbonate, and nickel chloride, preferably basic nickel carbonate; the cobalt source is one or more of cobalt nitrate, cobalt acetate, basic cobalt carbonate, and cobalt chloride, preferably basic cobalt carbonate. The phosphorus-containing compound is phosphoric acid.
[0054] According to the present invention, in the preparation method of the hydrodenitrogenation catalyst, the impregnation in step (6) adopts a spray impregnation method, and the impregnation adopts equal volume impregnation or supersaturated impregnation. Preferably, after the impregnation, the sample is placed under closed conditions at room temperature for 6 to 12 hours before the drying step is performed; in step (6), the drying condition is a constant temperature of 100 to 160° C. for 1 to 8 hours; the calcination condition is a constant temperature of 450 to 650° C. for 3 to 7 hours, preferably a constant temperature of 480 to 600° C. for 4 to 7 hours.
[0055] According to the present invention, in the grading method of the residue oil hydrogenation catalyst, the loading volume of the hydrodesulfurization catalyst accounts for 20% to 30% of the total catalyst loading volume. The loading volume of the hydrodenitrogenation catalyst accounts for 30% to 40% of the total catalyst loading volume. The loading volume of the hydrogenation protective agent accounts for 15% to 25% of the total catalyst loading volume. The loading volume of the hydrodemetallization catalyst accounts for 10% to 20% of the total catalyst loading volume.
[0056] According to the present invention, in the grading method of the residue oil hydrogenation catalyst, the loading volume of the hydrodesulfurization catalyst and the hydrodenitrogenation catalyst accounts for more than 50% of the total catalyst loading volume, preferably 50% to 70%.
[0057] According to the present invention, preferably, a foam ceramic catalyst can be loaded before the hydrogenation protective agent, and the loading volume of the foam ceramic catalyst accounts for 1% to 10% of the total catalyst loading volume.
[0058] According to the present invention, the foam ceramic catalyst, hydrogenation protectant and hydrodemetallization catalyst can be conventional catalysts in the art, generally using an alumina-based carrier with Group VIB and / or Group VIII metals as active metal components.
[0059] According to the present invention, the foam ceramic catalyst has a content of 0.5% to 2% of Group VIB metals in oxide form, and a content of 0.1% to 1.0% of Group VIII metals in oxide form, based on the weight of the catalyst.
[0060] According to the present invention, the hydrogenation protective agent, based on the weight of the catalyst, contains 1.5% to 6% of Group VIB metal in terms of oxide, and 0.4% to 3.0% of Group VIII metal in terms of oxide.
[0061] According to the present invention, the hydrodemetallization catalyst has a content of 3% to 14% of Group VIB metal in terms of oxide and a content of 0.5% to 5.0% of Group VIII metal in terms of oxide, based on the weight of the catalyst.
[0062] According to the present invention, the foam ceramic catalyst, hydrogenation protective agent and hydrogenation demetallization catalyst can be purchased commercially, such as the FZC series catalyst developed and produced by Sinopec Fushun Petrochemical Research Institute.
[0063] According to the present invention, the hydrodesulfurization catalyst and the hydrodenitrogenation catalyst need to be sulfurized before use, and conventional in-situ presulfurization or ex-situ presulfurization can be used.
[0064] According to the present invention, further, the sulfurization step includes: the catalyst is contacted with the sulfurizing liquid and hydrogen for sulfurization, and the sulfurization process is divided into two stages. The first stage: heating to 150-180°C and constant temperature sulfurization for 1-8 hours, and the second stage: heating to 250-340°C and constant temperature sulfurization for 1-8 hours.
[0065] According to the present invention, further, in the vulcanization method, the heating rate in the first stage is 0.1-5.0° C. / min; and the heating rate in the second stage is 0.5-5.0° C. / min.
[0066] According to the present invention, further, in the sulfurization method, the sulfurization liquid comprises a solvent and a sulfur-containing solute. The mass content of the sulfur-containing solute in the sulfurization liquid is 1.0% to 10.0%, preferably 2.0% to 8.0%.
[0067] According to the present invention, further, in the sulfurization method, the solvent is a liquid organic hydrocarbon. Among them, the liquid organic hydrocarbon is a hydrocarbon with a final boiling point of not higher than 300°C. Preferably, the solvent is selected from one or more of alkanes with a carbon number of 6 to 10 and distillate oils. The alkanes with a carbon number of 6 to 10 are preferably saturated hydrocarbons. The distillate oil is preferably a low-nitrogen distillate oil with a nitrogen content of not higher than 20μg / g.
[0068] According to the present invention, further, in the sulfurization method, the sulfur-containing solute includes at least one of CS2, dimethyl disulfide, dimethyl sulfoxide, tetramethyl sulfoxide, and dodecyl sulfide.
[0069] According to the present invention, further, in the sulfurization method, the amount of sulfurization liquid used is 0.5-6.0 g / h per gram of catalyst, preferably 1.0-5.0 g / h. The hydrogen gas is hydrogen gas with a purity of not less than 90v%.
[0070] According to the present invention, further, in the sulfurization method, the sulfurization conditions are as follows: the hydrogen pressure is 1.0 to 20.0 MPa, preferably 2.0 to 16.0 MPa; the hydrogen flow rate is 3 to 20 mL / min per gram of catalyst, preferably 5 to 15 mL / min.
[0071] The second aspect of the present invention provides application of the grading method in residual oil hydrogenation reaction.
[0072] According to the present invention, the application method is specifically as follows: under hydroprocessing reaction conditions, the residual oil is contacted with the catalyst loaded by the above-mentioned grading method to carry out a hydrogenation reaction to obtain a hydroprocessing product.
[0073] According to the present invention, in the application, the residual oil raw material includes at least one of atmospheric residual oil, vacuum residual oil and deasphalted oil.
[0074] According to the present invention, in the application, the operating conditions of each reaction zone are independently: reaction temperature is 340-400°C; reaction pressure is 6.0-25.0MPa; hydrogen-oil volume ratio is 200:1-1200:1; liquid hourly volume space velocity is 0.1-2.0h -1 .
[0075] According to the present invention, in the application, the residual oil hydrogenation reaction adopts a fixed bed hydrotreating process.
[0076] According to the present invention, the hydrogenated oil obtained by hydrotreating the residual oil is used as the feed of the catalytic cracking unit, or as the feed of the hydrocracking unit, or as the feed of the heavy oil deep catalytic cracking unit (DCC).
[0077] Compared with the prior art, the present invention has the following advantages:
[0078] 1. The fixed-bed hydrotreating method for residual oil of the present invention adopts the above-mentioned hydrodesulfurization catalyst and hydrodenitrogenation catalyst for graded filling, the particle size gradually decreases, the average pore size gradually decreases, the activity gradually increases, and the sulfide hydrogenation and nitride in the asphaltene can be deeply converted, the hydrogenation activity is high, and the stability is good.
[0079] 2. In the preparation process of the hydrodenitrogenation catalyst of the present invention, the impregnation solution containing alcohols, amines, thiourea and active metals can be used to complex the metal ions of Group VIII to form a complex, and simultaneously form phosphomolybdate (tungstate), and the Ga species located on the surface and near the surface area effectively prevent the formation of strong Mo(W)-O-Al bonds, thereby further leading to the weakening of the acidity adjustment and interaction between the active metal and the carrier, which is beneficial to make the hydrodesulfurization and denitrification catalysts have suitable acid amount and acid distribution, and the catalyst has strong anti-coking performance, which is beneficial to improve the hydrodesulfurization activity and stability.
[0080] 3. In the preparation process of the hydrodesulfurization catalyst of the present invention, firstly, metakaolin is subjected to hydrothermal treatment in the presence of gallium nitrate and ammonium fluoride for modification, and while the silicon-aluminum ratio is increased by dealumination, a species of gallium is introduced to form a Si-O-Ga bond, and due to the removal of aluminum, more coordinated unsaturated aluminum ions and silicon oxide on the surface of the silicon-aluminum material are exposed, and then the catalyst is prepared by combining with aluminum oxide, a pore-enlarging agent, etc. to form a carrier, and then the carrier is impregnated with an impregnation solution containing alcohols, amines, thiourea and active metals, so that the active metal ions in the impregnation solution and the mixture formed by the alcohols, amines and thiourea are in contact with the carrier, and the coordinated unsaturated sites and SH groups therein generate Lewis acids and The acid sites are concentrated to obtain a catalyst with suitable pore structure, high acid content and suitable acid strength distribution, which is particularly suitable for residue hydrodesulfurization.
[0081] In addition, during the preparation of the hydrodesulfurization catalyst, the Group VIII metal ions are made to form a complex and the Group VIB metals are made to form a phosphomolybdate (tungstate) structure, which helps to generate a high-quality active phase. DETAILED DESCRIPTION
[0082] The technical solution of the present invention is described in detail below in conjunction with embodiments.
[0083] In the present invention, the total infrared acid, L acid or B acid is determined by infrared spectroscopy, and the instrument is the American Nicot Fourier infrared spectrometer-6700. The determination method is as follows: weigh 20 mg of a sample with a particle size less than 200 mesh, press it into a thin sheet with a diameter of 20 mm, and install it on the sample holder of the absorption cell. Put 200 mg of the sample into the instrument hanging cup, connect the absorption cell and the adsorption tube, and evacuate the vacuum to a vacuum degree of 4×10 -2Pa, the temperature was raised to 500 ° C, maintained for 1 hour to remove the adsorbent on the sample surface, and then cooled to room temperature, pyridine was adsorbed to saturation, and the temperature was continued to rise to 160 ° C, balanced for 1 hour, and the physically adsorbed pyridine was desorbed to obtain the total infrared acid, B acid and L acid. The acid amount unit is mmol / g. Then the temperature was raised to 250 ° C, 350 ° C, and 450 ° C in turn, and each was balanced for 1 hour to obtain the corresponding infrared acid, B acid and L acid. Among them, the acid at 1450 cm -1 The absorption peak nearby is L acid, 1540cm -1 The absorption peak nearby is B acid.
[0084] In the present invention, the specific surface area, pore volume and pore distribution are measured by using the ASAP2420 fully automatic physical adsorption instrument of the American Micromeritics Instrument Company, and the measuring method is as follows: the sample is treated at 300°C and 0.1MPa for 4 hours, liquid N2 is used as the adsorbent, the adsorption temperature is -196°C, and the analysis test is performed after accurate weighing. The specific surface area is calculated according to the BET method, and the pore volume and pore distribution are calculated according to the BJH method.
[0085] In the present invention, the formulas for the hydrodesulfurization rate (HDS) and the hydrodenitrogenation rate (HDN) are as follows:
[0086] Hydrodesulfurization rate (HDS) = (S mass fraction in feedstock - S mass fraction in product) / S mass fraction in feedstock × 100%;
[0087] Hydrodenitrogenation rate (HDN) = (N mass fraction in feedstock - N mass fraction in product) / N mass fraction in feedstock × 100%.
[0088] Example 1
[0089] Take 360g of metakaolin, 88g of gallium nitrate, and 36g of ammonium fluoride, add 2520g of distilled water to the above materials and stir for 20 minutes, transfer the above materials into an autoclave and seal it, heat it to 80°C at a rate of 10°C / min and keep it at a constant temperature for 3 hours, then heat it to 110°C at a rate of 5°C / min and keep it at a constant temperature for 5 hours, filter and wash, then dry the material at 120°C for 6 hours, and then roast it at 600°C for 5 hours to obtain gallium and fluorine modified material I (the mass content of gallium is 3.6%, and the mass content of fluorine is 1.1%). Take 179g of pseudo-boehmite (the mass content of aluminum oxide is 69.1%), 269g of material I, 9g of sesbania powder, 4.5g of nitric acid, 3g of citric acid, 18g of activated carbon with a particle size of 4 microns, and 228g of water, mix and knead it into shape, dry it at 120°C for 3 hours, and roast it at 700°C for 4 hours to obtain catalyst carrier A-0.
[0090] Weigh 100g of catalyst carrier A-0, measure its water absorption rate to be 0.9, take 202g of molybdenum trioxide (containing 99wt% of molybdenum oxide), 96.2g of basic nickel carbonate (containing 52wt% of nickel oxide), 52.4g of phosphoric acid solution (containing 26.7wt% of phosphorus), add clean water and stir, gradually heat and boil until all the raw materials are dissolved, keep constant temperature for 40 minutes and then cool to room temperature for standby use to obtain an impregnation solution. Slowly add pentaerythritol, diethanolamine and thiourea mixture to the above solution under stirring, the mass ratio of pentaerythritol and diethanolamine is 3:1, the amount of thiourea added is to make its concentration in the impregnation solution 20g / L, the amount of pentaerythritol added is to make its concentration in the impregnation solution 16g / L, and the solution is fixed to 90mL for standby use. The above impregnation solution is impregnated on the carrier A-0 by spraying to obtain A-1. A-1 was placed in a sealed container at room temperature for 6 hours, dried at 120°C for 4 hours, and finally calcined at 550°C for 4 hours to obtain CA-1.
[0091] Example 2
[0092] Take 500g of metakaolin, 92g of gallium nitrate, and 25g of ammonium fluoride, add 4388g of distilled water to the above materials and stir for 30 minutes, transfer the above materials into an autoclave and seal it, heat it to 90°C at a rate of 8°C / min and keep it at a constant temperature for 4 hours, then heat it to 120°C at a rate of 10°C / min and keep it at a constant temperature for 3 hours, filter and wash, then dry the material at 130°C for 4 hours, and then roast it at 650°C for 4 hours to obtain gallium and fluorine modified material I (the mass content of gallium is 2.8%, and the mass content of fluorine is 1.3%). Take 146g of pseudo-boehmite (the mass content of aluminum oxide is 68.6%), 358g of material I, 12g of sesbania powder, 6g of nitric acid, 4g of citric acid, 22g of activated carbon with a particle size of 4 microns, and 304g of water, mix and knead it into shape, dry it at 130°C for 2 hours, and roast it at 730°C for 3 hours to obtain catalyst carrier B-0.
[0093] Weigh 100g of catalyst carrier B-0, measure its water absorption rate to be 0.88, take 182g of molybdenum trioxide (containing 99wt% of molybdenum oxide), 96.2g of basic nickel carbonate (containing 52wt% of nickel oxide), 59.9g of phosphoric acid solution (containing 26.7wt% of phosphorus), add clean water and stir, gradually heat and boil until all the raw materials are dissolved, keep constant temperature for 60 minutes and then cool to room temperature for standby use to obtain an impregnation solution. Slowly add 1,4-butanediol, ethylenediamine and thiourea mixture to the above solution under stirring, the mass ratio of 1,4-butanediol and ethylenediamine is 6:1, the amount of thiourea added is to make its concentration in the impregnation solution 32g / L, the amount of 1,4-butanediol added is to make its concentration in the impregnation solution 22g / L, and the solution is fixed to 88mL for standby use. The above impregnation solution is impregnated on the carrier B-0 by spraying to obtain B-1. B-1 was placed in a sealed container at room temperature for 8 hours, dried at 130°C for 2 hours, and finally calcined at 530°C for 3 hours to obtain CB-1.
[0094] Example 3
[0095] Take 600g of metakaolin, 102g of gallium nitrate, and 36g of ammonium fluoride, add 5540g of distilled water to the above materials and stir for 60 minutes, transfer the above materials into an autoclave and seal it, heat it to 80°C at a rate of 6°C / min and keep it at a constant temperature for 3 hours, then heat it to 130°C at a rate of 8°C / min and keep it at a constant temperature for 3 hours, filter and wash, then dry the material at 120°C for 3 hours, and then roast it at 600°C for 5 hours to obtain gallium and fluorine modified material I (the mass content of gallium is 2.6%, and the mass content of fluorine is 0.9%). Take 224g of pseudo-boehmite (the mass content of aluminum oxide is 69%), 538g of material I, 15g of sesbania powder, 7g of nitric acid, 5g of citric acid, 36g of activated carbon with a particle size of 4 microns, and 462g of water, mix and knead it into shape, dry it at 120°C for 2 hours, and roast it at 750°C for 3 hours to obtain catalyst carrier C-0.
[0096] Weigh 100g of catalyst carrier C-0, measure its water absorption rate to be 0.93, take 192g of molybdenum trioxide (containing 99wt% of molybdenum oxide), 101g of basic nickel carbonate (containing 52wt% of nickel oxide), 52.4g of phosphoric acid solution (containing 26.7wt% of phosphorus), add clean water and stir, gradually heat and boil until all the raw materials are dissolved, keep constant temperature for 60 minutes and then cool to room temperature for standby use to obtain an impregnation solution. Slowly add ethylene glycol, hexamethylenetetramine and thiourea mixture to the above solution under stirring, the mass ratio of ethylene glycol and hexamethylenetetramine is 4:1, the amount of thiourea input is to make its concentration in the impregnation solution 43g / L, the amount of ethylene glycol input is to make its concentration in the impregnation solution 19g / L, and the solution is fixed to 93mL for standby use. The above impregnation solution is impregnated on the carrier C-0 by spraying to obtain C-1. C-1 was placed in a sealed container at room temperature for 8 hours, dried at 120°C for 2 hours, and finally calcined at 500°C for 3 hours to obtain CC-1.
[0097] Example 4
[0098] Take 750g of metakaolin, 132g of gallium nitrate, and 44g of ammonium fluoride, add 5741g of distilled water to the above materials and stir for 90 minutes, transfer the above materials into an autoclave and seal it, heat it to 90°C at a rate of 5°C / min and keep it at a constant temperature for 4 hours, then heat it to 130°C at a rate of 8°C / min and keep it at a constant temperature for 3 hours, filter and wash, then dry the material at 140°C for 2 hours, and then roast it at 550°C for 5 hours to obtain gallium and fluorine modified material I (the mass content of gallium is 3.8%, and the mass content of fluorine is 1.0%). Take 251g of pseudo-boehmite (the mass content of aluminum oxide is 67.9%), 532g of material I, 15g of sesbania powder, 7g of nitric acid, 5g of citric acid, 36g of activated carbon with a particle size of 4 microns, and 462g of water, mix and knead it into shape, dry it at 120°C for 2 hours, and roast it at 750°C for 3 hours to obtain catalyst carrier D-0.
[0099] Weigh 100g of catalyst carrier D-0, measure its water absorption rate to be 0.93, take 192g of molybdenum trioxide (containing 99wt% of molybdenum oxide), 101g of basic nickel carbonate (containing 52wt% of nickel oxide), 52.4g of phosphoric acid solution (containing 26.7wt% of phosphorus), add clean water and stir to gradually heat and boil until all the raw materials are dissolved, keep constant temperature for 60 minutes and then cool to room temperature for standby use. Slowly add glycerol, ethanolamine and thiourea mixture to the above solution under stirring, the mass ratio of glycerol and ethanolamine is 6:1, the amount of thiourea input is to make its concentration in the impregnation solution 52g / L, the amount of glycerol input is to make its concentration in the impregnation solution 26g / L, and the solution is fixed to 93mL for standby use. The above impregnation solution is impregnated on the carrier D-0 by spraying to obtain D-1. D-1 was placed in a sealed container at room temperature for 8 hours, dried at 130°C for 3 hours, and finally calcined at 490°C for 3 hours to obtain CD-1.
[0100] Example 5
[0101] Take 360g of metakaolin, 88g of gallium nitrate, and 36g of ammonium fluoride, add 2520g of distilled water to the above materials and stir for 20 minutes, transfer the above materials into an autoclave and seal it, heat it to 110°C at a rate of 5°C / min and keep it at a constant temperature for 5 hours, filter and wash it, then dry it at 120°C for 6 hours, and then roast it at 600°C for 5 hours to obtain gallium and fluorine modified material I (the mass content of gallium is 3.6%, and the mass content of fluorine is 1.1%). Take 179g of pseudo-boehmite (the mass content of aluminum oxide is 69.1%), 269g of material I, 9g of sesbania powder, 4.5g of nitric acid, 3g of citric acid, 18g of activated carbon with a particle size of 4 microns, and 228g of water, mix and knead it into shape, dry it at 120°C for 3 hours, and roast it at 700°C for 4 hours to obtain catalyst carrier E-0.
[0102] Weigh 100g of catalyst carrier E-0, measure its water absorption rate to be 0.9, take 202g of molybdenum trioxide (containing 99wt% of molybdenum oxide), 96.2g of basic nickel carbonate (containing 52wt% of nickel oxide), 52.4g of phosphoric acid solution (containing 26.7wt% of phosphorus), add clean water and stir, gradually heat and boil until all the raw materials are dissolved, keep constant temperature for 40 minutes and then cool to room temperature for standby use to obtain an impregnation solution. Slowly add pentaerythritol, diethanolamine and thiourea mixture to the above solution under stirring, the mass ratio of pentaerythritol and diethanolamine is 3:1, the amount of thiourea added is to make its concentration in the impregnation solution 20g / L, the amount of pentaerythritol added is to make its concentration in the impregnation solution 16g / L, and the solution is fixed to 90mL for standby use. The above impregnation solution is impregnated on the carrier E-0 by spraying to obtain E-1. E-1 was placed in a closed container at room temperature for 6 hours, dried at 120°C for 4 hours, and finally calcined at 550°C for 4 hours to obtain CE-1.
[0103] Example 6
[0104] Take 100g NaY molecular sieve (properties are as follows: the molar ratio of silicon oxide to aluminum oxide is 6:1, and the sodium content is 7wt%), 20g ammonium chloride and 800g deionized water, mix and slurry, adjust the slurry pH≈3.5 with hydrochloric acid, ion exchange at 90°C for 2h, the number of ammonium ion exchanges is 2 times, and then filter and wash to obtain NH4Y molecular sieve filter cake; add 1500g deionized water to the obtained NH4Y molecular sieve filter cake, 3g citric acid, and 20g polyvinyl alcohol (molecular weight is 25000) to the above materials and stir evenly, transfer the above materials into an autoclave for hydrothermal treatment, and after sealing, heat to 100°C at a rate of 15°C / min and keep the temperature constant for 3 hours, then heat to 140°C at a rate of 10°C / min and keep the temperature constant for 6 hours, filter, wash, and then dry the material at 120°C for 6 hours to obtain a modified molecular sieve.
[0105] 179g of pseudo-boehmite (alumina mass content of 69.2%), 269g of modified molecular sieve, 9g of sesbania powder, 4.5g of nitric acid, 3g of citric acid, 12g of activated carbon with a particle size of 4 microns, and 178g of water were kneaded and formed, dried at 120°C for 3 hours, and calcined at 550°C for 3 hours to obtain catalyst carrier F. The obtained carrier F was saturated with 1.5mol / L gallium nitrate solution and treated at 100% water vapor and 550°C for 90min to obtain catalyst carrier F-0.
[0106] Weigh 100g of catalyst carrier F-0, measure its water absorption rate to be 0.9, take 202g of molybdenum trioxide (containing 99wt% of molybdenum oxide), 96.2g of basic nickel carbonate (containing 52wt% of nickel oxide), 52.4g of phosphoric acid solution (containing 26.7wt% of phosphorus), add clean water and stir, gradually heat and boil until all the raw materials are dissolved, keep constant temperature for 40 minutes and then cool to room temperature for standby use to obtain an impregnation solution. Slowly add pentaerythritol, diethanolamine and thiourea mixture to the above solution under stirring, the ratio of pentaerythritol to diethanolamine is 3:1, the amount of thiourea added is to make its concentration in the impregnation solution 20g / L, the amount of pentaerythritol added is to make its concentration in the impregnation solution 16g / L, and the solution is fixed to 90mL for standby use. The above impregnation solution is impregnated on the carrier F-0 by spraying to obtain F-1. F-1 was placed in a sealed container at room temperature for 6 hours, dried at 120°C for 4 hours, and finally calcined at 500°C for 4 hours to obtain CF-1.
[0107] Example 7
[0108] Take 200g NaY molecular sieve (properties are as follows: the molar ratio of silicon oxide to aluminum oxide is 4:1, and the sodium content is 11wt%), 40g ammonium chloride and 1400g deionized water, mix and slurry, adjust the slurry pH≈4 with nitric acid, ion exchange at 85°C for 3h, the number of ammonium ion exchanges is 2 times, and then filter and wash to obtain NH4Y molecular sieve filter cake; add 4000g deionized water to the above materials, stir evenly, transfer the above materials into an autoclave for hydrothermal treatment, seal and heat to 110°C at a rate of 10°C / min and keep the temperature constant for 2.5 hours, then heat to 130°C at a rate of 10°C / min and keep the temperature constant for 6 hours, filter and wash; then dry the material at 120°C for 4 hours to obtain a modified molecular sieve.
[0109] 147g of pseudo-boehmite (alumina mass content of 68.7%), 359g of modified molecular sieve, 12g of sesbania powder, 6g of nitric acid, 4g of citric acid, 22g of activated carbon with a particle size of 4 microns, and 258g of water were kneaded and formed, dried at 140°C for 3 hours, and calcined at 550°C for 3 hours to obtain catalyst carrier G. The obtained carrier G was saturated with 2.0 mol / L gallium nitrate solution and treated at 100% water vapor and 550°C for 70 minutes to obtain catalyst carrier G-0.
[0110] Weigh 100g of catalyst carrier G-1, measure its water absorption rate to be 0.88, take molybdenum trioxide (containing 99wt% molybdenum oxide) 183g, basic nickel carbonate (containing 52wt% nickel oxide) 96.2g, phosphoric acid solution (containing 26.7wt%) 59.9g, add clean water and stir to gradually heat and boil until all the raw materials are dissolved, keep constant temperature for 60 minutes and then cool to room temperature for standby use. Slowly add 1,4-butanediol and diethanolamine and thiourea mixture to the above solution under stirring, the ratio of 1,4-butanediol to diethanolamine is 5:1, the amount of thiourea input is 33g / L in the impregnation solution, the amount of 1,4-butanediol input is 22g / L in the impregnation solution, and the solution is fixed to 88mL for standby use. The above impregnation solution is impregnated on the carrier G-0 by spraying to obtain G-1. G-1 was placed in a sealed container at room temperature for 8 hours, dried at 120°C for 4 hours, and finally calcined at 490°C for 4 hours to obtain CG-1.
[0111] Example 8
[0112] Take 152g NaY molecular sieve (properties are as follows: the molar ratio of silicon oxide to aluminum oxide is 5:1, and the sodium content is 7wt%), 46g ammonium chloride and 1672g deionized water, mix and slurry, adjust the slurry pH≈3.5 with nitric acid, perform ion exchange at 90°C for 3h, the number of ammonium ion exchanges is 2 times, and then filter and wash to obtain NH4Y molecular sieve filter cake; add 3200g deionized water to the obtained NH4Y molecular sieve filter cake, 5g adipic acid, and 17g polyvinyl pyrrolidone (molecular weight is 30000) to the above materials and stir evenly, transfer the above materials into an autoclave for hydrothermal treatment, seal and heat to 110°C at a rate of 10°C / min and keep the temperature constant for 4 hours, then heat to 130°C at a rate of 10°C / min and keep the temperature constant for 6 hours, filter and wash; then dry the material at 130°C for 4 hours to obtain a modified molecular sieve.
[0113] 251g of pseudo-boehmite (alumina mass content of 69%), 532g of modified molecular sieve, 9g of sesbania powder, 4.5g of nitric acid, 3g of citric acid, 17g of activated carbon with a particle size of 4 microns, and 328g of water were kneaded and formed, dried at 130°C for 4 hours, and calcined at 650°C for 3 hours to obtain catalyst carrier H. The obtained carrier H was saturated with 1.7 mol / L gallium nitrate solution and treated at 100% water vapor and 600°C for 60 minutes to obtain catalyst carrier H-0.
[0114] Weigh 100g of catalyst carrier H-1, measure its water absorption rate to be 0.9, take 202g of molybdenum trioxide (containing 99wt% of molybdenum oxide), 96.2g of basic nickel carbonate (containing 52wt% of nickel oxide), 52.4g of phosphoric acid solution (containing 26.7wt% of phosphorus), add clean water and stir, gradually heat and boil until all the raw materials are dissolved, keep constant temperature for 40 minutes and then cool to room temperature for standby use. Slowly add pentaerythritol, diethanolamine and thiourea mixture to the above solution under stirring, the ratio of pentaerythritol to diethanolamine is 3:1, the amount of thiourea input is to make its concentration in the impregnation solution 20g / L, the amount of pentaerythritol input is to make its concentration in the impregnation solution 19g / L, and the solution is fixed to 90mL for standby use. The above impregnation solution is impregnated on the carrier H-0 by spraying to obtain H-1. After H-1 was placed in a sealed container at room temperature for 6 hours, it was dried at 120°C for 4 hours and finally calcined at 550°C for 4 hours to obtain CH-1.
[0115] Example 9
[0116] Take 100g NaY molecular sieve (properties are as follows: the molar ratio of silicon oxide to aluminum oxide is 7:1, and the sodium content is 10wt%), 25g ammonium chloride and 800g deionized water, mix and slurry, adjust the slurry pH≈3.5 with hydrochloric acid, ion exchange at 90°C for 2h, the number of ammonium ion exchanges is 3 times, and then filter and wash to obtain NH4Y molecular sieve filter cake; add 1500g deionized water to the obtained NH4Y molecular sieve filter cake, 3g citric acid, and 20g methyl cellulose (molecular weight is 20000) to the above materials and stir evenly, transfer the above materials into an autoclave for hydrothermal treatment, and after sealing, heat to 100°C at a rate of 15°C / min and keep the temperature constant for 3 hours, then heat to 140°C at a rate of 10°C / min and keep the temperature constant for 6 hours, filter and wash; then dry the material at 120°C for 6 hours to obtain a modified molecular sieve.
[0117] 224g of pseudo-boehmite (alumina mass content of 67.8%), 538g of modified molecular sieve, 15g of sesbania powder, 7g of nitric acid, 5g of citric acid, 36g of activated carbon with a particle size of 4 microns, and 462g of water were kneaded and formed, dried at 120°C for 3 hours, and calcined at 550°C for 3 hours to obtain catalyst carrier I. The obtained carrier I was saturated with 1.5mol / L gallium nitrate solution and treated at 100% water vapor and 600°C for 80min to obtain catalyst carrier I-0.
[0118] Weigh 100g of catalyst carrier I-1, measure its water absorption rate to be 0.93, take molybdenum trioxide (containing 99wt% molybdenum oxide) 192g, basic nickel carbonate (containing 52wt% nickel oxide) 102g, phosphoric acid solution (containing 26.7wt%) 52.4g, add clean water and stir to gradually heat and boil until all the raw materials are dissolved, keep constant temperature for 70 minutes and then cool to room temperature for standby use. Slowly add neopentyl glycol, hexamethylenetetramine and thiourea mixture to the above solution under stirring, the ratio of neopentyl glycol to hexamethylenetetramine is 4:1, the amount of thiourea input is to make its concentration in the impregnation solution 39g / L, the amount of neopentyl glycol input is to make its concentration in the impregnation solution 27g / L, and the solution is fixed to 93mL for standby use. The above impregnation solution is impregnated on the carrier I-0 by spraying to obtain I-1. I-1 was placed in a sealed container at room temperature for 6 hours, dried at 120°C for 4 hours, and finally calcined at 495°C for 4 hours to obtain CI-1.
[0119] Example 10
[0120] Take 100g NaY molecular sieve (properties are as follows: the molar ratio of silicon oxide to aluminum oxide is 6:1, and the sodium content is 7wt%), 20g ammonium chloride and 800g deionized water, mix and slurry, adjust the slurry pH≈3.5 with hydrochloric acid, ion exchange at 90°C for 2h, the number of ammonium ion exchanges is 2 times, and then filter and wash to obtain NH4Y molecular sieve filter cake; add 1500g deionized water to the obtained NH4Y molecular sieve filter cake, 3g citric acid, and 20g polyvinyl alcohol (molecular weight is 25000) to the above materials and stir evenly, transfer the above materials into an autoclave for hydrothermal treatment, heat to 140°C at a rate of 10°C / min and keep constant for 6 hours, filter and wash, and then dry the material at 120°C for 6 hours to obtain a modified molecular sieve.
[0121] 179g of pseudo-boehmite (alumina mass content of 69.2%), 269g of modified molecular sieve, 9g of sesbania powder, 4.5g of nitric acid, 3g of citric acid, 12g of activated carbon with a particle size of 4 microns, and 178g of water were kneaded and formed, dried at 120°C for 3 hours, and calcined at 550°C for 3 hours to obtain catalyst carrier J. The obtained carrier J was saturated with 1.5mol / L gallium nitrate solution and treated at 100% water vapor and 550°C for 90min to obtain catalyst carrier J-0.
[0122] Weigh 100g of catalyst carrier J-1, measure its water absorption rate to be 0.9, take 202g of molybdenum trioxide (containing 99wt% of molybdenum oxide), 96.2g of basic nickel carbonate (containing 52wt% of nickel oxide), 52.4g of phosphoric acid solution (containing 26.7wt% of phosphorus), add clean water and stir, gradually heat and boil until all the raw materials are dissolved, keep constant temperature for 40 minutes and then cool to room temperature for standby use to obtain an impregnation solution. Slowly add pentaerythritol, diethanolamine and thiourea mixture to the above solution under stirring, the ratio of pentaerythritol to diethanolamine is 3:1, the amount of thiourea added is to make its concentration in the impregnation solution 20g / L, the amount of pentaerythritol added is to make its concentration in the impregnation solution 16g / L, and the solution is fixed to 90mL for standby use. The above impregnation solution is impregnated on carrier J-0 by spraying to obtain J-1. J-1 was placed in a sealed container at room temperature for 6 hours, dried at 120°C for 4 hours, and finally calcined at 500°C for 4 hours to obtain CJ-1.
[0123] Examples 11-15
[0124] The catalyst obtained in Example 1-10 was vulcanized, and the vulcanization process was as follows: the catalyst was loaded into a tubular reactor and pre-sulfurized. The vulcanizing liquid was a cyclohexane solution of CS2 with a mass fraction of 5.0%. The flow rate of the vulcanizing liquid was 2.1 g / h per gram of catalyst, the pressure of hydrogen was 5.0 MPa, and the flow rate of hydrogen was 10 mL / min per gram of catalyst. The reaction was divided into two temperature sections. The first stage started from 80° C., the heating rate was 2.0° C. / min, and the temperature was kept constant at 160° C. for 4.0 h; the second stage started from 160° C., the heating rate was 2.0° C. / min, and the temperature was kept constant at 300° C. for 2.0 h, and the vulcanization was completed.
[0125] The catalyst obtained after sulfidation in Example 1-10 is graded and loaded. The properties of the residual oil raw material used are shown in Table 4. A fixed bed process is adopted. Foam ceramic catalyst, hydrogenation protective agent, hydrodemetallization catalyst, hydrodesulfurization catalyst, and hydrodenitrification catalyst are sequentially loaded along the flow direction of the liquid phase. Based on the total catalyst loading volume ratio, the loading volumes of the foam ceramic catalyst, hydrogenation protective agent, hydrodemetallization catalyst, hydrodesulfurization catalyst, and hydrodenitrification catalyst are 5%, 20%, 15%, 25%, and 35%, respectively. The foam ceramic catalyst, hydrogenation protective agent, and hydrodemetallization catalyst are all produced by Sinopec Fushun Petrochemical Research Institute. The models are: foam ceramic catalyst (FGF-02), hydrogenation protective agent (FZC-100B), and hydrodemetallization catalyst (FZC-204A). The grading method parameters of the hydrodesulfurization catalyst and the hydrodenitrification catalyst are shown in Tables 5-1 to 5-3.
[0126] The operating conditions of each reaction zone are: reaction temperature 350℃, reaction pressure 7.5MPa, hydrogen-to-oil volume ratio 550:1, liquid hourly volume space velocity 0.5h -1 The evaluation results of the reactions are shown in Tables 5-1 to 5-3.
[0127] Comparative Example 1
[0128] Compared with Example 1, the comparative hydrodesulfurization catalyst DCA-1 was prepared by mixing and kneading the metakaolin without modification with pseudo-boehmite and the like to prepare a carrier.
[0129] Comparative Example 2
[0130] Compared with Example 1, the comparative hydrodesulfurization catalyst DCA-2 was prepared by simply mechanically mixing and modifying the metakaolin, gallium nitrate and ammonium fluoride without transferring the above materials into an autoclave for sealed hydrothermal treatment.
[0131] Comparative Example 3
[0132] Compared with Example 1, pentaerythritol, diethanolamine and thiourea mixture were not added during the preparation of the impregnation solution, and the conventional impregnation solution was impregnated on the carrier to prepare a comparative hydrodesulfurization catalyst DCA-3.
[0133] Comparative Example 4
[0134] Compared with Example 1, thiourea was not added during the preparation of the impregnation solution, and the impregnation solution I containing pentaerythritol and diethanolamine was impregnated on the carrier to prepare a comparative hydrodesulfurization catalyst DCA-4.
[0135] Comparative Example 5
[0136] Compared with Example 1, the metakaolin was only modified with gallium, and no ammonium fluoride was added. The amounts of other materials and the preparation conditions were the same as those in Example 1, and a comparative hydrodesulfurization catalyst DCA-5 was prepared.
[0137] Comparative Example 6
[0138] Compared with Example 1, the metakaolin was only fluorine-modified without adding gallium nitrate, and the amounts of other materials and the preparation conditions were the same as those in Example 1, thereby obtaining a comparative hydrodesulfurization catalyst DCA-6.
[0139] Comparative Example 7
[0140] Compared with Example 6, the comparative hydrodenitrogenation catalyst DCF-1 was prepared by mixing and kneading the NH4Y molecular sieve directly with pseudo-boehmite etc. to prepare a carrier without adding organic acid and water-soluble polymer for modification.
[0141] Comparative Example 8
[0142] Compared with Example 6, the comparison hydrodenitrogenation catalyst DCF-2 was prepared except that the catalyst carrier was not immersed in the gallium nitrate solution and subjected to high-temperature steam treatment.
[0143] Comparative Example 9
[0144] Compared with Example 6, pentaerythritol, diethanolamine and thiourea mixture were not added during the preparation of the impregnation solution, and the conventional impregnation solution I was impregnated on the carrier to prepare the comparative hydrodenitrogenation catalyst DCF-3.
[0145] Comparative Example 10
[0146] Compared with Example 6, thiourea was not added during the preparation of the impregnation solution, and the impregnation solution I containing pentaerythritol and diethanolamine was impregnated on the carrier to prepare a comparative hydrodenitrogenation catalyst DCF-4.
[0147] Comparative Examples 11-20
[0148] The catalysts obtained in Comparative Examples 1-10 were sulfurized using the same method as in Examples 11-15.
[0149] The catalysts obtained from comparative examples 1-10 after sulfidation were graded and loaded. The properties of the residual oil raw materials used are shown in Table 4. A fixed bed process was used. Foam ceramic catalyst, hydrogenation protective agent, hydrodemetallization catalyst, hydrodesulfurization catalyst, and hydrodenitrification catalyst were sequentially loaded along the flow direction of the liquid phase. Based on the total catalyst loading volume ratio, the loading volume ratios of the foam ceramic catalyst, hydrogenation protective agent, hydrodemetallization catalyst, hydrodesulfurization catalyst, and hydrodenitrification catalyst were 5%, 20%, 15%, 25%, and 35%, respectively. Foam ceramic catalyst, hydrogenation protective agent, and hydrodemetallization catalyst were all produced by Sinopec Fushun Petrochemical Research Institute. The models are: foam ceramic catalyst (FGF-02), hydrogenation protective agent (FZC-100B), and hydrodemetallization catalyst (FZC-204A). The grading method parameters of hydrodesulfurization catalyst and hydrodenitrification catalyst are shown in Tables 5-1 to 5-3.
[0150] The operating conditions of each reaction zone are: reaction temperature 350℃, reaction pressure 7.5MPa, hydrogen-to-oil volume ratio 550:1, liquid hourly volume space velocity 0.5h -1 The evaluation results of the reactions are shown in Tables 5-1 to 5-3.
[0151] Table 1-1 Example catalyst composition and properties
[0152] project Example 1 Example 2 Example 3 Example 4 Example 5 composition <![CDATA[MoO3,wt%]]> 15.2 15.8 15.4 15.6 15.5 NiO, wt% 3.7 3.9 3.8 3.6 3.7 nature <![CDATA[Specific surface area, m 2 / g]]> 187 185 192 188 181 <![CDATA[Pore volume, cm 3 / g]]> 0.52 0.59 0.57 0.61 0.50 Average pore size, nm 11.45 10.66 11.29 13.18 10.09
[0153] Table 1-2 Example catalyst composition and properties
[0154] project Example 6 Example 7 Example 8 Example 9 Example 10 composition <![CDATA[MoO3,wt%]]> 18.2 18.8 18.4 18.4 18.5 NiO, wt% 4.7 4.9 4.8 4.8 4.6 nature <![CDATA[Specific surface area, m 2 / g]]> 215 207 232 197 194 <![CDATA[Pore volume, cm 3 / g]]> 0.52 0.59 0.47 0.55 0.57 Average pore size, nm 11.9 12.2 13.7 11.3 11.9
[0155] Table 1-3 Comparative Example Catalyst Composition and Properties
[0156]
[0157]
[0158] Table 1-4 Comparative Example Catalyst Composition and Properties
[0159] project Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 composition <![CDATA[MoO3,wt%]]> 15.9 15.2 18.6 18.1 18.9 18.8 NiO, wt% 3.5 3.1 4.5 4.7 4.8 4.6 nature <![CDATA[Specific surface area, m 2 / g]]> 168 171 157 168 195 189 <![CDATA[Pore volume, cm 3 / g]]> 0.43 0.46 0.33 0.43 0.47 0.44 Average pore size, nm 8.20 9.30 7.9 9.7 9.6 10.1
[0160] Table 2-1 Properties of modified Y molecular sieves in various examples and comparative examples
[0161] nature Example 6 Example 7 Example 8 Example 9 Example 10 Crystal size, nm 463 436 391 401 495 <![CDATA[Molar ratio of SiO2 / Al2O3]]> 25 19 31 37 10 <![CDATA[Specific surface area, m 2 / g]]> 705 668 683 711 643 Unit cell parameters, nm 2.442 2.453 2.449 2.452 2.435 Average pore size, nm 12.5 11.9 11.1 12.4 10.3
[0162] Table 2-2 Properties of modified Y molecular sieves in various embodiments and comparative examples
[0163] nature Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 Crystal size, nm 658 461 472 456 <![CDATA[Molar ratio of SiO2 / Al2O3]]> 7 21 23 24 <![CDATA[Specific surface area, m 2 / g]]> 382 598 630 625 Unit cell parameters, nm 2.128 2.448 2.446 2.444 Average pore size, nm 8.2 10.8 10.9 12.2
[0164] Table 3 Infrared acid properties of catalysts in various embodiments and comparative examples
[0165]
[0166]
[0167] Table 4 Raw oil properties and reaction conditions
[0168] project nature Raw oil properties <![CDATA[Density / kg·m -3 > 970.0 S / wt% 2.2 N / wt% 0.54 <![CDATA[Ni+V / μg·g -1 ]]> 72 Reaction conditions Reaction temperature / ℃ 350 Pressure / MPa 7.5 <![CDATA[Space velocity per hour -1 > 0.5 Hydrogen to oil volume ratio 550
[0169] Table 5-1 Catalyst activity evaluation results
[0170]
[0171] Table 5-2 Catalyst activity evaluation results
[0172]
[0173]
[0174] Table 5-3 Catalyst activity evaluation results
[0175] project Operation time,h Comparative Example 17 Comparative Example 18 Comparative Example 19 Comparative Example 20 Desulfurization catalyst number / CA-1 CA-1 CA-1 CA-1 Denitrification catalyst number / DCF-1 DCF-2 DCF-3 DCF-4 HDS, % 2000 43.8 / / / HDN, % 2000 51.2 / / / HDS, % 200 67.2 68.9 70.2 73.1 HDN, % 200 76.2 77.5 81.7 79.2
[0176] From the catalyst evaluation results, the desulfurization and denitrification performances of the catalyst grading method of the present invention are better than those of the comparative example.
Claims
1. A grading method for a residue oil hydrogenation catalyst, comprising: Along the flow direction of the liquid phase, a hydrogenation protective agent, a hydrodemetallization catalyst, a hydrodesulfurization catalyst and a hydrodenitrogenation catalyst are sequentially filled; The hydrodesulfurization catalyst comprises a carrier and an active metal component, wherein the carrier comprises gallium- and fluorine-modified metakaolin and alumina in a mass ratio of 15-30:7-13; the gallium content of the gallium- and fluorine-modified metakaolin is 2.0%-5.0% by mass, and the fluorine content is 0.8%-1.5% by mass.
2. The grading method according to claim 1, characterized in that: The hydrodenitrogenation catalyst comprises a carrier and an active metal component. The carrier comprises a modified Y molecular sieve and alumina. The modified Y molecular sieve is a small-grain mesoporous modified Y molecular sieve with the following properties: a crystal particle size of less than 500 nm, preferably 300 to 500 nm, a molar ratio of silicon oxide to alumina of 8 to 55, a specific surface area of 640 to 800 m 2 / g, the unit cell parameters are 2.433~2.460nm, and the average pore size is 10~30nm.
3. The grading method according to claim 1, characterized in that: The loading volume of the hydrodesulfurization catalyst accounts for 20% to 30% of the total catalyst loading volume; The packing volume of the hydrodenitrogenation catalyst accounts for 30% to 40% of the total catalyst packing volume; The filling volume of the hydrogenation protection agent accounts for 15% to 25% of the total catalyst filling volume; The loading volume of the hydrodemetallization catalyst accounts for 10% to 20% of the total catalyst loading volume.
4. The grading method according to claim 1 or 3, characterized in that: The loading volume of the hydrodesulfurization catalyst and the hydrodenitrogenation catalyst accounts for more than 50% of the total catalyst loading volume, preferably 50% to 70%.
5. The grading method according to claim 1, characterized in that: The hydrogenation protectant and / or the hydrodemetallization catalyst uses an alumina-based carrier and has Group VIB and / or Group VIII metals as active metal components; Furthermore, the hydrogenation protection agent, based on the weight of the catalyst, has a content of 1.5% to 6% of Group VIB metal in terms of oxide, and a content of 0.4% to 3.0% of Group VIII metal in terms of oxide; And / or, the hydrodemetallization catalyst has a content of 3% to 14% of Group VIB metal in terms of oxide, and a content of 0.5% to 5.0% of Group VIII metal in terms of oxide, based on the weight of the catalyst.
6. The grading method according to claim 1, characterized in that: The properties of the hydrodesulfurization catalyst are as follows: the specific surface area is 180 to 220 m 2 / g, the pore volume is 0.5~0.7mL / g, and the average pore diameter is 10.0~30.0nm.
7. The grading method according to claim 1 or 6, characterized in that: The preparation method of the hydrodesulfurization catalyst comprises: (1) mixing metakaolin, gallium nitrate, ammonium fluoride and water, sealing and hydrothermally treating, drying and calcining to obtain a modified material; (2) kneading the modified material obtained in step (1), pseudo-boehmite, an adhesive, an extrusion aid, a pore-enlarging agent and water, drying and calcining to obtain a catalyst carrier; (3) preparing an impregnation solution containing amines, alcohols, thiourea and active metals; (4) The catalyst carrier obtained in step (2) is impregnated with the impregnation solution obtained in step (3), and the catalyst carrier is dried and calcined to obtain a hydrodesulfurization catalyst.
8. The grading method according to claim 7, characterized in that: In the preparation method of the hydrodesulfurization catalyst, the mass ratio of the gallium nitrate and the ammonium fluoride in step (1) is 1 to 10:1, and the total mass of the gallium nitrate and the ammonium fluoride accounts for 5% to 60% of the mass of the metakaolin, preferably 15% to 40%; and / or, the amount of water added in step (1) is such that the mass ratio of water to the total mass of the metakaolin, gallium nitrate and ammonium fluoride is 5:1 to 10:
1.
9. The grading method according to claim 7, characterized in that: In the preparation method of the hydrodesulfurization catalyst, the conditions of the sealed hydrothermal treatment in step (1) are as follows: the hydrothermal treatment temperature is 80-130°C and the time is 3-10 hours; preferably, the hydrothermal treatment adopts a two-stage hydrothermal treatment, and the temperature of the second stage is at least 20°C higher than the temperature of the first stage, preferably at least 30°C higher.
10. The grading method according to claim 7, characterized in that: In the preparation method of the hydrodesulfurization catalyst, the alcohol compound in step (3) is one or more of pentaerythritol, ethylene glycol, propylene glycol, 1,2-propylene glycol, 1,4-butylene glycol, and neopentyl glycol; the amine compound is one or more of hexamethylenetetramine, ethylenediamine, ethanolamine, diethanolamine, and triethanolamine; the mass ratio of the alcohol compound to the amine compound is 1:1 to 16:1; the amount of thiourea added is such that its concentration in the impregnation solution is 5 to 70 g / L, preferably 8 to 50 g / L; the concentration of the alcohol compound in the impregnation solution in step (3) is 5 to 60 g / L, preferably 7 to 30 g / L.
11. The grading method according to claim 2, characterized in that: In the hydrodenitrogenation catalyst, the active metal includes at least one metal component selected from Group VIII and at least one metal component selected from Group VIB; the Group VIII metal is preferably nickel and / or cobalt, and the Group VIB metal is preferably molybdenum and / or tungsten.
12. The grading method according to claim 11, characterized in that: Based on the mass of the catalyst, the mass content of the carrier is 74% to 85%, the content of Group VIII in terms of oxide is 2% to 6%, and the content of Group VIB metal in terms of oxide is 15% to 24%; based on the mass of the carrier, the content of modified Y molecular sieve is 40% to 70%, and the content of aluminum oxide is 14% to 40%.
13. The grading method according to claim 2 or any one of claims 10 to 12, characterized in that: The preparation method of the hydrodenitrogenation catalyst comprises: (1) The NaY molecular sieve is subjected to ammonium ion exchange, filtration and washing to obtain an NH4Y molecular sieve filter cake; (2) mixing the NH4Y molecular sieve filter cake obtained in step (1) with an organic acid, a water-soluble polymer and water, and then performing a hydrothermal treatment to obtain a modified Y molecular sieve; (3) kneading the modified Y molecular sieve obtained in step (2), pseudo-boehmite, an adhesive, an extrusion aid, a pore-enlarging agent and water into a mold, drying and calcining to obtain a catalyst carrier; (4) impregnating the catalyst support obtained in step (3) into a gallium nitrate solution, drying it, and subjecting it to high-temperature steam treatment to obtain a catalyst support; (5) preparing an impregnation solution containing amines, alcohols, thiourea and active metals; (6) The catalyst carrier obtained in step (4) is impregnated with the impregnation solution obtained in step (5), and the mixture is dried and calcined to obtain a hydrodenitrogenation catalyst.
14. The grading method according to claim 13, characterized in that: In the preparation method of the hydrodenitrogenation catalyst, the properties of the NaY molecular sieve in step (1) are as follows: the molar ratio of silicon oxide to aluminum oxide is 3-7:1, and the sodium content is 6wt%-12wt%; the ammonium ion exchange of the NaY molecular sieve in step (1) is to mix the NaY molecular sieve with an ammonium salt solution and slurry it, adjust the pH value of the slurry, perform ammonium ion exchange, filter and wash to obtain an NH4Y molecular sieve filter cake; wherein the mass ratio of NaY molecular sieve: water: ammonium salt is 1:6-25:0.2-0.4; the pH value of the slurry is adjusted to 3-4; the ammonium ion exchange temperature is adjusted to 70-90°C, the ammonium ion exchange time is 2-4 hours, and the number of ammonium ion exchanges is 1-3 times.
15. The grading method according to claim 13, characterized in that: In the preparation method of the hydrodenitrogenation catalyst, the organic acid in step (2) is selected from at least one of fumaric acid, adipic acid, tartaric acid, citric acid, oxalic acid, acetic acid, salicylic acid and malic acid, and the water-soluble polymer is selected from at least one of polyvinyl alcohol, polyethylene oxide, polyvinyl pyrrolidone and water-soluble polysaccharides having a weight average molecular weight of 10,000 to 40,000; and / or, the mass ratio of NH4Y molecular sieve: organic acid: water-soluble polymer: water in step (2) is 1: 0.01 to 0.05: 0.05 to 0.25: 15 to 40.
16. The grading method according to claim 13, characterized in that: In the preparation method of the hydrodenitrogenation catalyst, the conditions of the hydrothermal treatment in step (2) are as follows: the temperature is 100-150°C and the treatment time is 5-12 hours; preferably, the hydrothermal treatment adopts a two-stage hydrothermal treatment, and the temperature of the second stage is at least 15°C higher than the temperature of the first stage, preferably at least 20°C; and / or, the hydrothermal treatment in step (2) is followed by drying, and the drying conditions are as follows: the drying temperature is 100-160°C and the drying time is 3-8 hours.
17. The grading method according to claim 13, characterized in that: In the preparation method of the hydrodenitrogenation catalyst, the mass ratio of the pseudo-boehmite in step (3) calculated as alumina to the modified Y molecular sieve is 7-13:15-30; the amount of the pore expanding agent added is 2wt%-10wt% of the total mass of the pseudo-boehmite in step (3) calculated as alumina and the modified Y molecular sieve; and / or the drying temperature in step (3) is 120-160°C, the drying time is 3-6 hours, the calcination temperature is 550-700°C, and the calcination time is 2-6 hours.
18. The grading method according to claim 13, characterized in that: In the preparation method of the hydrodenitrogenation catalyst, the concentration of the gallium nitrate solution in step (4) is 0.5 to 2.5 mol / L; the impregnation method in step (4) is saturated impregnation or unsaturated impregnation; the conditions of the high-temperature steam treatment are as follows: the temperature is 500 to 700° C. and the time is 60 to 90 min.
19. The grading method according to claim 13, characterized in that: In the preparation method of the hydrodenitrogenation catalyst, the alcohol compound in step (5) is one or more of pentaerythritol, ethylene glycol, propylene glycol, 1,2-propylene glycol, 1,4-butylene glycol, and neopentyl glycol; the amine compound is one or more of hexamethylenetetramine, ethylenediamine, ethanolamine, diethanolamine, and triethanolamine; the mass ratio of the alcohol compound to the amine compound is 1:1 to 16:1; the amount of thiourea added is such that its concentration in the impregnation solution is 5 to 70 g / L, preferably 8 to 50 g / L; in the impregnation solution in step (5), the concentration of the alcohol compound is 2 to 60 g / L, preferably 7 to 30 g / L.
20. Use of the grading method according to any one of claims 1 to 19 in residual oil hydrogenation reaction.
Citation Information
Patent Citations
Method for preparation of hydrofining catalyst
CN1098433A
Residual oil hydrogenation catalyst and preparation method and use thereof
CN101491764A
Catalyst for hydro-denitrification of inferior heavy distillate oil and preparation method and application of catalyst
CN103212432A
Hydrocarbon oil desulfurization catalyst and application method thereof
CN104209142A
Residual oil hydrotreatment catalyst grading method and residual oil hydrotreatment method
CN105567312A
Cited By
Residual oil hydrogenation catalyst as well as preparation method and application thereof
CN121623822A